Liability For Corporate Crimes In Environmental Crimes In Indonesia (Case Study Of Pt. Wijaya Inti Nusantara) - Taufiq, Muhammad (Faculty of Law, Universitas Pekalongan, 2024)
Corporate Crime is a serious crime that harms the people of Indonesia, especially in the long term. For a long time, corporate crime has often been in the public spotlight, especially with cases such as corruption, money laundering, and tax evasion. Not only that, in the environmental aspect there are also corporate crimes, for example in the abuse of power that causes environmental pollution which has a very wide impact on various parties. Therefore, this study aims to examine how the criminal liability of corporations that commit environmental crimes in Indonesia is carried out. The research methodologyused here is normative juridical research. The results of the research obtained are criminal liability for environmental crimes committed by corporations, accountability not only for individuals, but also corporations such as for example a business entity as emphasized in Articles 116-118 of Law No. 32 of 2009. As well as providing a perspective on how Islamic law responds to the phenomenon of corporate criminal liability. In this case, Islamic Law has views from various sources, namely the Qur'an and As-Sunnah as the main reference in managing the environment and behaving. In Surah Ar-Rum verse 40 Allah Subhanahu Wa Ta'ala said: It has been seen that the destruction on the land and in the sea is caused by the deeds of human hands (Through it) Allah makes them feel a part of their deeds so that they can return (to the right path). The MUI in its Fatwa once stated that in the utilization of environmental wealth, managers must prioritize ethics that avoid environmental damage not only for the sake of profit. In Islamic law, corporate liability in the environment is to compensate for losses due to unlawful acts.